Kebolehan penyelesaian persamaan linear: satu kerangka dalam penaksiran bilik darjah - Lim, Hooi Lian; Wun, Thiam Yew; Idris, Noraini (UUM College of Arts and Sciences, 2009)
Purpose – This paper discussed the development of a framework based on SOLO model (Structure of the Observed Learning Outcome) to characterise students’ linear equation solving ability in arithmetic sequence domain. Method – This study is categorised as a case study. Data of this study was collected using clinical interview technique. Subjects of this study consisted of nine Form Four students. Two out of eight interview tasks constructed as instrument of this research involved the arithmetic sequence domain. Findings – Six levels of linear equation solving ability in solving arithmetic sequence tasks, namely prestructural level, unistructural level, multistructural level, lower relational level, upper relational level, and extended abstract level were identified. The validity related to the assessment and refinement of descriptors in the framework had shown the high consistency and correspondence between the framework and the subjects’ responses. Value – This study extends the mathematics education literature(especially in assessment field) about the effectiveness of SOLO model in developing an assessment framework to assess student’s solving ability in linear equation.